Taxis, passengers and stable marriage-stable simultaneous assignment of taxis to passenger booking re-quests - Kümmel, Michal (2018)
This thesis deals with the challenge of dispatching taxis to passenger booking requests. The main contribution is the methodology which assigns and re-assigns groups of taxis to groups of passenger booking requests and reflects the interest of not just taxis but also passengers, and which produces stable assignments. The proposed methodology is de-signed for a centralized system that assigns and re-assigns the bookings simultaneously in decision epochs in real-time. The solution to the stable marriage algorithm, originally designed for matching men and women according to their preferences, is applied to dis-patching taxis to passenger booking requests. The proposed methodology is evaluated in a custom-made taxi simulation model. The results indicate that the proposed taxi dis-patching strategies outperform a commonly used first-come, first-served dispatching strategy in a number of performance indicators (e.g. passenger waiting time and taxi distance) as well as for various combinations of advance and immediate booking requests.